“Estudo fitoquímico e ensaios biológicos com Leandra lacunosa (Melastomataceae)” - Arantes, Glenda Marqueti (2007)
The present work describes the phytochemical studies and the evaluation trypanocidal and the hypoglycemic activities of the aerial parts of the plant species Leandra lacunosa (Melastomataceae). Isolation and the purification of the substances were carried out through chromatographic methods and structural elucidations were accomplished by means of spectroscopic methods (1H-NMR, 13C NMR and MS), besides gas-liquid chromatography. The hydroalcoholic extract afforded the flavonoids quercetin, kaempherol, and luteolin, besides the triterpene ursolic acid. GC-MS analysis allowed the identification of the steroid tremulone (Stigmasta-3,5-dien-7-one). Trypanocidal activity in vitro tests were developed with the crude extract, fractions (bioassay-guided fractionation) and isolated flavonoids. The hydrocoholic extract and the isolated flavonoids exhibited low activity in the assay against the tripomastigotas forms of the Trypanosoma cruzi. However, the triterpene ursolic acid displayed significant trypanocidal effect, confirming the previous results for this substance. The hydroalcoholic extract of L. lacunosa gave rise to significant results in several model assays used in the evaluation of the hypoglycemic activity, thus confirming the popular use of the plant in some states of the Brazilian northeastern region. Key-words: Leandra lacunosa; Melastomataceae; trypanocidal activity, hypoglycemic activity.